Underwater manipulator that imitates the movements of the human arm - Babiarz, Artur; Bieda, Robert; Borowik, Tomasz; Grzejszczak, Tomasz; Hartwig, Tomasz; Jaskot, Krzysztof; Kozyra, Andrzej; Ściegienka, Piotr (Frontiers in Marine Science, 2023)
In this paper, the design of a five degrees of freedom (5DoF) underwater manipulator system is presented and discussed. The forward and inverse kinematics problem are solved and shown. Additionally, a system that mimics the human arm movements using a manipulator is proposed. In order to imitate the movement of the human arm, the layout diagram of the IMU sensors and the method of first calibration were presented. The work also presents a device with a simple haptic feedback used to facilitate control of the gripper. The presented approach to the design of a robot control system is dedicated to an underwater robot with the main assumption of reducing the complexity of the system. Taking into account the authors' knowledge, this approach distinguishes the presented system from solutions known from the literature.